Characterization and mechanism of early hydration of calcium aluminate cement with anatase-TiO2 nanospheres additive. (20th November 2020) - Guo, Chunyu; Wang, Enhui; Hou, Xinmei; Chen, Junhong; Zhang, Wensheng; Ye, Jiayuan; Qin, Shouwan
Highlights: Effects of different contents of nano-TiO2 on the hydration of CAC are studied. Nano-TiO2 can largely shorten the induction period in the CAC hydration process. Nano-TiO2 contributes to the formation of small size lamellar hydration products. The promotion mechanism of nano-TiO2 on the hydration of CAC is proposed. Abstract: Aiming to shorten the hydration time of calcium aluminate cement (CAC) at 20 ℃, anatase-TiO2 nanospheres (nano-TiO2 ) additive at the content range from 1 to 5% (mass percent) was added in CAC with water to cement ratio ( w / c ) of 0.4. Isothermal calorimetry in combination with conductimetric measurements, TG-DTA, XRD, optical microscopy and SEM were adopted to investigate the heat change, ion concentration change, phase and microstructure of CAC samples during the early hydration. The results show that the main hydration products of CAC added with nano-TiO2 change from CaAl2 O4 ·10H2 O (CAH10 ) and Ca2 Al2 O5 ·8H2 O (C2 AH8 ) to CAH10, with no presence of other new phases. Nano-TiO2 can promote the hydration process of CAC. However the promotion effect varies depending on its content. Especially, the end time of induction period and early hydration period with 3% nano-TiO2 addition are shortened by 4 h and 6 h, respectively. Based on this, the hydration promotion mechanism of nano-TiO2 additive is further clarified from the point of vacancy and nucleation.